THE EFFECT OF USING PICTURE TO PREDICT INFORMATION TOWARDS STUDENTS READING COMPETENCE IN READING DESCRIPTIVE TEXT - Akasendo Fadhil Ahmad; Melyann Melani (Universitas Pahlawan Tuanku Tambusai, 2022)
There are some problems in this research first, the students’ lack of vocabulary makes the students difficult to comprehend the written form. This problem also produces another problem. Students do not even know the meaning of the title from a certain text. The next problem is they do not have a good strategy in reading and they were not motivated in learning English.This research used quantitative as the approach and experimental as the design of the research. Researcher chose the Pretest Posttest non-equivalent control Design. The population from this research is 117 students that are the total of the students in the 8th grade in SMPN 2 Kapur IX and the sample of this research will be determined by using purposive sampling which was VIII.A and VIII.D.Based on the finding of the research, it has proven that the using picture to predict information toward students’ test result in reading descriptive text gave significant difference on students’ test result. The mean of post-test of experimental class was 72 and control class was 65.